Dyslexia-friendly practice in the secondary classroom - Mortimore, Tilly; Dupree, Jane.; Sage eBooks (Exeter : Learning Matters, 2008)
Written specifically for trainee and newly-qualified teachers this standards-based text explores the needs of dyslexic learners in mainstream secondary schools.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Dyslexic children -- Education (Secondary) -- Great Britain; Inclusive education -- Great Britain; Electronic books